Introducing the conflict sensitivity wheel - Medina, Leonardo (2025)
Climate adaptation can unintentionally deepen tensions in fragile settings. This blog introduces the Conflict Sensitivity Wheel, a practical framework for assessing how adaptation policies interact with power, participation, and inequality, and how they can be redesigned to reduce conflict and support sustainable peace.